Adaptation: A Promising Metaphor for Strategic Management - Chakravarthy, Balaji S. (Academy of Management Review, 1982)
Strategic management is the process through which a manager ensures the long term survival and growth of a firm. This paper provides a comprehensive framework for strategic management based on adaptation, a metaphor that succinctly captures the endeavors of an organization to be fitted better to its environment.